Інсулінома: випадок із лікарської практики - Станкова, Н. І.; Ляшук, П. М.; Грабовецький, О. В.; Ляшук, Р. П.; Леонова, М. О. (Clinical Endocrinology and Endocrine Surgery, 2011)
The work describes a clinical case of hypoglycemic syndrome caused by insulinoma of pancreas. Surgical ablation of tumor resulted in abatement of the illness symptoms.